x-2=6x-4

Simple and best practice solution for x-2=6x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-2=6x-4 equation:



x-2=6x-4
We move all terms to the left:
x-2-(6x-4)=0
We get rid of parentheses
x-6x+4-2=0
We add all the numbers together, and all the variables
-5x+2=0
We move all terms containing x to the left, all other terms to the right
-5x=-2
x=-2/-5
x=2/5

See similar equations:

| -3.21+4.27x=-7.48 | | 2n-3/2-3n-8/4=n+1/3 | | 23.4-x=0.25x | | b×4=24 | | 12x-13=611 | | 4x+15=171 | | -13x=-7x+6x5 | | 5{5x+4}=45 | | (2x+5)(x-1)=(x+2)(x+1) | | 3x/12=69 | | 9^x-4x3^x-1+27=0 | | 5x+4=203x | | x*360/3400=9 | | x360/3400=9 | | 11x-3=68 | | 3x+2(x-1)=2x+4 | | 7X^2-100x-60000=0 | | 7X^2-100x-6000=0 | | 7X^2-100x+6000=0 | | X^2-100x-6000=0 | | 6x+2=4x–12 | | a+(3/2a)+2a+6a=1400 | | 20­3x=2x-5 | | a+3/2a+2a+6a=1400 | | m^2-3m+2.25=0 | | 6x2-30=0 | | 23x-17=19+x | | 9x^2-19x-6=65 | | 6d+4d+3d+d=1400 | | x-19=2x+14 | | 7x=3x­-1 | | 4x+14-3x=17x |

Equations solver categories